Incidence of pressure injuries in the postoperative period of cardiac surgeries (Research, Society and Development, 2023)
Objective: To identify the incidence of Pressure Injury in patients admitted to cardiac surgery upon admission to the Intensive Care Unit. Method: Cross-sectional and prospective study. Performed in the postoperative period of Adult Cardiac Surgery in a large public hospital. The sample of this study is composed of 99 patients through their own initiative. Data collection was carried out by filling out a semi-structured form containing sociodemographic and health variables, postoperative variables and those related to pressure injuries through the information received via the patient's electronic medical record. Result: In the present study, an incidence of pressure injury of 8.1% is evident, with the most gradual classifications at university level II (62%), followed by degree I (50%), deep tissue pressure injury (25 %) and finally, injuries not classifiable and by medical devices with 12%. As for the affected site, the sacral region was identified (75%), followed by the left and right calcaneus, left gluteal (25% in each) and other sites such as the right gluteal, labial, trochanter, malleolus and occipital (12%). Mortality was higher in patients who developed pressure injuries and the main reason for not being postoperative was the presence of arrhythmia. Conclusion: The findings showed the existence of an association between pressure injuries in clinical conditions and procedures performed in the postoperative period of cardiac surgery. Whit that, the nurse's prior knowledge of predictors and complications to alleviate the occurrence of pressure injuries is essential to improve the quality of life and patient safety.